A phenomenological meaning of testifying about suffering within an African Pentecostal church context : exploring narratives of black South African women's lived experience - Nyoka, Ayanda (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.